Robust Optimization of SC-FDE-Based Multihop DF Relay Systems With Imperfect CSI - Wu, Peiran; Li, Xiuhua (IEEE transactions on vehicular technology, 2017)
In this paper, we consider the robust transceiver optimization for a single-carrier frequency-domain equalization (SC-FDE)-based multihop half-duplex decode-and-forward (DF) relay system under imperfect channel state information (CSI). The goal is to maximize the system achievable bit rate (ABR) and to minimize the end-to-end bit error rate (BER) subject to a joint node power constraint. Due to the lack of analytical tractable expressions for ABR and BER under imperfect CSI, we resort to lower bounds of the hopwise ABRs and BERs and reformulate the original problem by using two approximated objective functions based on these lower bounds. For the reformulated problems, we show that the optimal equalization filters take the form of robust Wiener filters. Subsequently, we propose two efficient decentralized algorithms to obtain the optimal solutions for the resulting power-allocation problems. Numerical results are provided to confirm the ABR and BER performance of the proposed robust relaying schemes.